(3MdjI GdUaGJ aj GdCSeGA hGdUfGYGJs - (3jhSa Hf JZQj HQOj Hf YHO Gddg GdXGgQj GdMfaj, CHh GdeMGSf , GHf JZQj HQOj , LeGd GdOjf, J (B874 (3g` s ((3eMeO Hf eMehO Hf Ndjd GdMdHj GdMfaj s)
(3ChdgG (B:s
(3GdMeO ddg GdPj CMSf NdbfG HUfYg hPcQJ YOI ebGWjY ef CHjGJ aUGM, aj GdUfGYGJ hCSeGA GdedGM, Ydi Cffj ChQOJ ajg ef hGgj GdTYQ eG dG jYLHfj, dGeJgGfg hGfMWGWg Yf ceGd QJHI GdHdGZI hfbUGfg s
(3BNQgG (B:s
(3Ch de jfg Gdfgi Yf YOdg RGhjG hLg bHhd GdfUM Rj s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B222 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B282s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B265 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B690s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs